Increasing Student Learning Motivation Using Inquiry Methods in Chemistry Lessons - Endang Ningsih (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This research aims to describe increasing students' learning motivation using the inquiry method in chemistry subjects in Class X of Public High School 6 South Bengkulu. Methodology: In this research, the subjects were class X C students at Public High School 6 South Bengkulu, totaling 41 students. The object of this research is the application of inquiry methods in learning. The type of data obtained from this research is qualitative data. This data was collected using observation and documentation techniques. The data collection tools used were tests, observation sheets of teacher and student activities. Description The action research procedure was carried out in 2 cycles. Each cycle consists of planning, implementation, observation and reflection. Indicators of success are shown by the fulfillment of predetermined motivation indicators. Main Findings: In cycle I, indicator achievement was only 16.67%, while in cycle II achievement was 100% of the indicators set by the author and based on the targets set by the author. Based on the results of the research above, it can be concluded that using inquiry strategies can increase students' learning motivation in class. Novelty/Originality of this study: The novelty of this research is to determine the effectiveness of increasing student learning motivation by using the inquiry method in chemistry lessons.